India and EFTA: Pioneering novel FDI commitments - James J. Nedumpara; Pushkar Reddy (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
The investment chapter of the Trade and Economic Partnership Agreement concluded between India and EFTA includes a ground breaking commitment - EFTA to achieve specific investment and employment generation targets and India to foster investment friendly conditions. This Perspective explores how the trading partners can meet these shared objectives.
Keywords: 330